The Categorization of Documents Using Support Vector Machines - Khanduja, Daljeet Kaur; Kaur, Surjeet (International Journal of Scientific Research in Computer Science and Engineering, 2023)
Support vector machine (SVM) is a popular machine learning algorithm. It first converts the input data into a higher dimensional space using a collection of mathematical operations known as kernels, and then it classifies the data points into discrete clusters. In this paper we use a dataset that correlates to scientific article abstracts. The articles fall into four categories: astro-physics, computer science, math, physics. This paper`s goal is to use support vector machines (SVM) to predict a given document`s category based on its text. Then, it will compare the accuracy and F-Score of each SVM`s performance using a linear, polynomial, Gaussian radial basis function kernel. Subsequently, SVM is utilized as a binary classifier for classification tasks, and the classification algorithms` performance is assessed using the confusion matrix. The trade-off between the model`s sensitivity and specificity is compared and visualized using the receiver operating characteristic (ROC) curve, which is a measure of a classifier`s prediction quality.